Mechanism of Adefovir, Tenofovir and Entecavir Resistance: Molecular Modeling Studies of How A Novel Anti-HBV Agent (FMCA) Can Overcome the Drug Resistance - K. Rawal, R.; K. Konreddy, A.; K. Chu, C. (Current Medicinal Chemistry, 2015)
Regardless of significant improvement in the area of anti-HBV therapy, resistance and cross-resistance against available therapeutic agents are the major consideration in drug discovery of new agents. The present study is to obtain the insight of the molecular basis of drug resistance conferred by the B and C domain mutations of HBV-polymerase on the binding affinity of four anti-HBV agents [Adefovir (ADV), Tenofovir (TNF), Entecavir (ETV) & 2′-Fluoro-6′-methylene-carbocyclic adenosine (FMCA)]. In this regard, homology modeled structure of HBV polymerase was used for minimization, conformational search and Glide XP docking followed by binding energy calculation on wild-type as well as on mutant HBV-polymerases (N236T, L180M+M204V+S202G & A194T). Our studies suggest a significant correlation between the fold resistances and the binding affinity of anti-HBV nucleosides. The domain B residue, L180 is indirectly associated with other active-site hydrophobic residues such as A87, F88 and M204, whereas the domain C residue, M204 is closely associated with sugar/pseudosugar ring positioning in the active site. These hydrophobic residues can directly influence the interaction of the incoming nucleoside triphosphates and change the binding efficacy. The carbohydrate ring part of natural substrate dATP, dGTP, FMCA and ETV, are occupied in similar passion in the grooves of HBV polymerase active site. The exocyclic double bond of Entecavir and FMCA occupies in the backside hydrophobic pocket (made by residues A87, F88, L180and M204), which enhances the overall binding affinity. Additional hydrogen bonding interaction of 2’-fluorine of FMCA with R41 residue of polymerase promotes a positive binding in wild-type as well as in ADVr, ETVr and TNFr with respect to that of entecavir.
Keywords: nucleoside